EVALUATION OF THE VIEWS OF TOP MANAGERS AND WORKERS WHO WORK IN THE HEADQUARTER OF MINISTRY OF NATIONAL EDUCATION ON RESTRUCTURE - Ömür ÇOBAN; Servet Özdemir (International Journal of Eurasia Social Sciences, 2018)
Aim. The aim of the study is to examine the views of top managers and workers that work in the Headquarter of Ministry of National Education on restructure (MoNE). Method. The qualitative method was used in this study. The views of top managers in MoNE on restructure were collected via semi-structured interview form. Moreover, focus group interview was held with a group of nine participants (two chefs, a teacher who works in the headquarter of MoNE, two educationalists, a branch manager, an inspector, a head manager and two MoNE educational assistant experts).Findings. In this qualitative research, content analysis was conducted and the themes after the analysis were very close to the organizational change management model of Tushman and O’Reilly. The themes of the analysis were human, culture, structure, task, strategical choices and managerial leadership; and the restructure of MoNE was evaluated via these themes.Results. When the findings related to these themes were examined, it was seen that participation in the decision making process of organizational changing was poor, the effects of change on workers were ignored, the model after the change processes was not well built, uneasiness was the dominant factor in the changing period, there was no environment of trust, organizational memory was destructed and there was no effective monitoring and evaluation mechanism. It could be said that the positive sides of the changing process were that the bulky body of MoNE decreased, the positions and criteria of MoNE educational assistant experts were organised via legal regulations, and overlap of works was more ordinate.